Facility Location - Frank, Christian (Algorithms for Sensor and Ad Hoc Networks, 2007)
The facility location problem has occupied a central place in operations research since the early 1960’s, as it models design decisions on the placement of factories, warehouses, schools, or hospitals to serve a set of customers efficiently. For an overview of previous work see the survey chapter by Cornuejols, Nemhauser & Wolsey in [289]. Recently, it has received renewed research interest because it can be used to place servers or proxies in communication networks [380]. We apply the facility location problem to configuration and deployment issues in wireless sensor networks.More specifically, we discuss how algorithms for the facility location problem can be used to assign functionality to certain nodes in a wireless sensor network, i.e., choose a subset of designated nodes as service providers of a particular service.